The next threat to grid reliability-data security. - Jones, D.A (IEEE spectrum)
The authors describe how the growing reliance of the electric power industry on information technologies introduces a new class of cyber vulnerability. The principal challenge is to determine how best to counter cyber threats posed by malicious elements, be they terrorists bent on destruction, vandals hacking their way into control or data exchange systems, or even commercial competitors, stealing their adversaries' data or sabotaging their operations. They argue that the key to meeting that challenge successfully is to recognize the mutually supportive roles public and private sectors can play